WRKY Genes Improve Drought Tolerance in Arachis duranensis - Zhang, Yongli; Du, Pei; Xiong, Faqian; Zhang, Xiaojun; Song, Hui (Frontiers in Plant Science, 2022)
WRKY transcription factor participates in plant growth and development and response to biotic and abiotic stresses. Arachis duranensis, a turfgrass, has high drought tolerance, yet little is known about AdWRKYs response to drought stress in A. duranensis. In this study, RNA-seq identified five AdWRKYs, including AdWRKY18, AdWRKY40, AdWRKY42, AdWRKY56, and AdWRKY64, which were up-regulated under drought stress. Orthologous relationships between AdWRKYs and Arabidopsis WRKY were determined to predict the regulatory networks of the five AdWRKYs based on AtWRKYs. Additionally, protein-protein interactions were predicted using differentially expressed proteins from RNA-seq. The qRT-PCR results showed that AdWRKY40 was up-regulated, while AdWRKY42, AdWRKY56, and AdWRKY64 were down-regulated at different time points under drought stress. The predicted regulatory networks showed that AdWRKY40 activates COR47, RD21, and RD29A expression under drought stress. Besides, AdWRKY56 regulated CesA8 under drought stress. Aradu.YIQ80 (NAC019) interacted with AdWRKY40, AdWRKY42, AdWRKY56, and AdWRKY64, while Aradu.Z5H58 (NAC055) interacted with AdWRKY42 and AdWRKY64 under drought stress. This study used Arabidopsis to assess AdWRKYs function and regulatory networks, providing a basis for understanding drought tolerance in A. duranensis.